2011
DOI: 10.1212/wnl.0b013e318231526a
|View full text |Cite
|
Sign up to set email alerts
|

Presymptomatic spinal cord neurometabolic findings in SOD1 -positive people at risk for familial ALS

Abstract: Objective: It has been speculated that amyotrophic lateral sclerosis (ALS) is characterized by a premanifest period during which neurodegeneration precedes the appearance of clinical manifestations. Magnetic resonance spectroscopy (MRS) was used to measure ratios of neurometabolites in the cervical spine of asymptomatic individuals with a mutation in the SOD1 gene (SOD1ϩ) and compare their neurometabolic ratios to patients with ALS and healthy controls. Methods:A cross-sectional study of 1 H-MRS of the cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…The pathological processes underlying ALS begin before the first clinical symptoms become apparent [34,35,36,37]. Our data imply that deficits in executive functioning, in those patients who develop them, emerge in this pre-symptomatic phase and, unlike motor impairments, remain relatively stable after the initial decline.…”
Section: Discussionmentioning
confidence: 76%
“…The pathological processes underlying ALS begin before the first clinical symptoms become apparent [34,35,36,37]. Our data imply that deficits in executive functioning, in those patients who develop them, emerge in this pre-symptomatic phase and, unlike motor impairments, remain relatively stable after the initial decline.…”
Section: Discussionmentioning
confidence: 76%
“…There are inconsistent reports of structural and functional MRI abnormalities prior to symptom onset in those at high genetic risk of ALS [Carew et al, 2011; Menke et al, 2016; Ng et al, 2008; Vucic et al, 2008; Walhout et al, 2015]. Evidence of cortical hyperexcitability in asymptomatic carriers of genetic mutations who are “at risk” of ALS is restricted to a very limited finding of reduced ligand [ 11 C]‐flumazenil binding in two individuals with the D90A SOD1 mutation [Turner et al, 2005a], and three SOD1 mutation carriers who demonstrated reduced or absent intra‐cortical inhibition within three months of symptom onset [Vucic et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…23 Additionally, a recent cross-sectional MRS study of the cervical cord revealed differences in tissue metabolites (e.g., reduced NAA/Cr) in SOD1ϩ carriers compared to controls. 27 The expected heterogeneity of the study population with respect to the anticipated latency to onset of disease may underlie these varying cross-sectional findings.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%